Analysis of clozapine and norclozapine concentrations in adult patients with schizophrenia - Panić, Bojana; Jovanović, Marija; Lukić, Vera; Bulat, Zorica; Vučićević, Katarina; Miljković, Branislava; Milovanović, Srdjan (Archives of Pharmacy, 2022)
The atypical antipsychotic clozapine (CLZ) is primarily used for the treatment-resistant schizophrenia. Due to low therapeutic index and high pharmacokinetic variability, therapeutic drug monitoring (TDM) is highly recommended (1). The aim of this retrospective study was to analyze TDM data of CLZ and its active metabolite norclozapine (NCLZ) in adult patient with schizophrenia. The study included CLZ TDM data obtained from 69 patients (22-67 years) treated at the Clinic for Psychiatry, Clinical Center of Serbia, while NCLZ data were available from 43 patients. Serum concentrations were determined at the Institute of Forensic Medicine, Belgrade, Serbia using liquid chromatography with tandem mass spectrometry (LC-MS/MS). Statistical analysis was performed by SPSS software® (version 18). The daily doses of CLZ ranged between 37.5 and 600 mg. The mean value of CLZ and NCLZ levels were 0.285 ± 0.174 mg/L and 0.189 ± 0.132 mg/L, respectively. 73.06% and 26.83% of measured CLZ and NCLZ concentrations were outside reference range (mostly below), respectively. Significant positive correlation (p